(untitled) (Journal of Economic Research & Business Administration, 2019)
This article discusses issues related to the assessment of the investment attractiveness and competitiveness of a company, in particular, on the example of a soft drinks sector company. The dependence of investment attractiveness and competitiveness on the size and composition of value added was established and confirmed, and the sequence of methods for analyzing value added was clarified and indicators reflecting the current state and position of the company in the market were specified. We calculate Economic Value Added and its components using pyramidal metrics system INFA which was also developed for Czech companies. The objective is to see through its decomposition the weaker or stronger spots of the company in the analyzed period. The objective is to confirm that only financially healthy companies, producing EVA, can be competitive in the long run. We show the Czech INFA metrics system can serve as a very useful indicator for competitiveness analysis of this Kazakhstan company.